Accuracy and Reliability Study of the Simplified Nutritional Assessment Questionnaire (SNAQ) in Turkish Patients in Nutritional Evaluation - Kevser KUTLU TATAR; Rıdvan SİVRİTEPE; Sema UÇAK BASAT (Namık Kemal Tıp Dergisi, 2021)

(untitled)
Aim:This study aims to reveal the accuracy and reliability of Simplified Nutritional Assessment Questionnaire (SNAQ), which is a test relatively simple and easy to apply, in the Turkish population.Materials and Methods:This study was planned as monocentric and prospective. Patients who were hospitalized in the internal medicine ward and over 65 years old participated in the study. Since there is no SNAQ test in Turkish, its English version was translated into Turkish by a certified translator, and then translated back into English again for verification. The sample size of the study was determined as 200 patients. For each patient included in the study, Mini Nutritional Assessment, Nutritional Risk Screening-2002 and SNAQ tests were applied.Results:Participants consisted of 51% female and 49% male. 55.5% were at the age between 65 and 74 years, 23.5% were between 75 and 84 years, and 21% were over 85 years old. The reliability coefficient of the SNAQ test was found as 0.86. This value satisfied the lower limit criterion of 0.60 proposed in the literature.Conclusion:Turkish SNAQ was validated and proved to be reliable for the nutritional evaluation of the geriatric Turkish patient population.